Microbe- and danger-induced inflammation. Issue 2 (February 2015) - Broggi, Achille; Granucci, Francesca
Highlights Microbial stimuli induce the activation of both innate and adaptive immunity. Danger signals induce the activation of inflammation and wound healing. Microbe- and danger-induced inflammatory processes have different characteristics.